Another Look at Models of the Short-Term Interest Rate - Brenner, Robin J.; Harjes, Richard H.; Kroner, Kenneth F. (Journal of Financial and Quantitative Analysis, 1996)
Robin J. Brenner, Richard H. Harjes, Kenneth F. Kroner, Another Look at Models of the Short-Term Interest Rate, The Journal of Financial and Quantitative Analysis, Vol. 31, No. 1 (Mar., 1996), pp. 85-107